Perception of effort under fatigue and control of pacing in young swimmers - Scurati, R.; Michielon, G.; Longo, S.; Invernizzi, P. L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Pacing strategy is critical in middle- and long- distance performances to administer the power production related to the energy lost during the competition. In swimming, positive, negative, and even pacing approaches are then used. They suppose that the swimmer has an accurate and conscious perception of the effort (Borg, 1982), to properly manage his pace. The aim of this study was to observe how fatigue can alter the pacing in swimming, with relation to the perception of the effort. Methods: Ten swimmers (12.2±0.5 years, 47.0±5.5 kg, 159±1.0 cm, 18.56±1.36 kg/m^2) volunteered to be included in the study. Pushing-off from the wall, the participants performed 50m front crawl at 100% of their maximum velocity and, after 2 minutes of recovery, a second 50m at 90% of their maximum velocity (step 1). Afterwards, once performing a fatiguing task (i.e. 2000m front crawl at the anaerobic threshold velocity), the swimmers repeated the 50m front crawl trials, as before (step 2). Perceived exertion, assessed through the CR10 scale before and after every 50m, as well as stroke length (SL), stroke rate (SR) and velocity (v), have been compared. Results: At 100% of the maximum velocity, CR10 measured after the 50m trial was higher in step 2 than in step 1 (p<0.01; 5.1±1.3 vs. 7.3±0.7, AU). On the contrary, SR and v decreased after the fatiguing task (p<0.01, 0.97±0.06 vs. 0.91±0.05 cycles•s-1 and p<0.001, 1.49±0.07 vs. 1.40±0.10 m/s, SR and v, respectively). SL did not change. At 90% of the maximum velocity, CR10 was higher in step 2 than in step 1 both before (p<0.01, 5.1±1.3 vs. 7.3±0.8, AU) and after (p<0.05, 6.2±1.2 vs. 7.6±1.1, AU) the 50m trial. SR and v decreased (p<0.05, 0.87±0.06 vs. 0.82±0.06 cycles/s and p<0.01, 1.42±0.10 vs. 1.33±0.09 m/s, SR and v, respectively), whereas SL did not change. Discussion: The drop of the velocity and the increase of the perceived exertion, measured every 500m during the long swimming effort, confirmed that fatigue raised (Knicker et al, 2011). As swimmers experienced after the fatiguing task an overall worsening of both the perceived exertion and the biomechanics parameters, it could be deduced that fatigue affected the 50m trials and, as a consequence, the ability to address to the pace. Therefore, the training of swimming pacing after fatiguing tasks might be recommended in order to practice the perception of proper pace and to manage it, even when fatigue raises and interferes on its administration.